2015
DOI: 10.1016/j.jcis.2015.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Self-limiting adsorption of Eu3+ on the surface of rod-shape anatase TiO2 nanocrystals and post-synthetic sensitization of the europium-based emission

Abstract: The surface of oleic acid stabilized rod-shape anatase TiO2 nanocrystals was modified by adsorption of Eu(3+) ions. The Eu(3+) attachment showed Langmuir adsorption behavior, thus the loading of Eu(3+) could be controlled precisely up to surface saturation coverage. The Eu(3+)-TiO2 nanorods show weak Eu(3+) based luminescence. However, addition of thenoyltrifluoroacetone (TTFA) leads to coordination of the ligand to the Eu(3+) centers and the TTFA-Eu(3+)-TiO2 materials exhibit strong Eu(3+) fluorescence sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…We had previously demonstrated a procedure that allowed precise control of the adsorption of transition metal or lanthanide ions on the surface of TiO 2 nanocrystals. , We were motivated to show similar behavior on the surface of MnO nanocrystals. However, initial experiments in order to determine adsorption of Cu 2+ on MnO nanocrystals showed the unexpected result of formation of hollow nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…We had previously demonstrated a procedure that allowed precise control of the adsorption of transition metal or lanthanide ions on the surface of TiO 2 nanocrystals. , We were motivated to show similar behavior on the surface of MnO nanocrystals. However, initial experiments in order to determine adsorption of Cu 2+ on MnO nanocrystals showed the unexpected result of formation of hollow nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…In previous work, we established a robust protocol for the adsorption of metal ions onto the surface of TiO 2 nanorods as a synthesis method. 34,36,37 The reaction is self-limiting based on the number of surface titanium atoms on the nanocrystal. In the example of Co 2+ adsorbed onto the surface of TiO 2 we observe nearly quantitative uptake of Co 2+ for Co : Ti mass ratio below $0.12, and above this ratio there is no additional uptake.…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported the quantitative attachment of transition-metal (Cr 3+ , Mn 2+ , Fe 2+ , Co 2+ , Ni 2+ , and Cu 2+ ) and lanthanide ions to the surface of rod-shaped TiO 2 nanocrystals and have shown that the adsorption of metal ions to the surface of a nanocrystal is potentially competitive with the selective nucleation of metal nanoparticles on the surface of nanocrystals . Complementary to our experimental studies, we have embarked on parallel theoretical investigations of model systems that consist of a transition-metal ion bound to the surface of TiO 2 . Calculated electronic structure and photoexcitation dynamics have revealed important findings.…”
Section: Introductionmentioning
confidence: 88%